Women and the Law - Atkins, Susan (OBServing Law, 2018)
Women And The Law is a pioneering study of the way in which the law has treated women - at work, in the family, in matters of sexuality and fertility, and in public life. Originally published in 1984, this seminal text is one that truly deserves its 'groundbreaking' moniker. Predating many key moments in contemporary feminist history, it was written before Judith Butler's Gender Trouble; before Naomi Klein's The Beauty Myth, with the term 'feminist jurisprudence' having only been coined three years earlier. It went on to inspire a legion of women lawyers and feminist legal rulings, from the Family Law Act 1996 to the legal definition of 'violence' (Yemshaw v. LB Hounslow 2011). This 2018 edition comes with a new foreword by Susan Atkins and provides a timely analysis of women in law forty years on, how much has changed and the work still left to do.